KONSEKUENSI PENERAPAN TEORI KOMUNIKASI DALAM KEGIATAN PEMBELAJARAN TATAP MUKA - Adi, Waluyo (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Communication theory is very helpful in the success of face-to-j(1ce learning activity. Therefore, the consequences of this theory to meet the entire requirement must be accomplished Main component of this theory are communicator (educator), communication (student), context (learning environment), n;r ssage (learning material) and delivery system (methods and media). Educators are the most significant component, as they are required to have the ability and the trust from students. This is naiVe if educators are not able to pack learning material attractively and choose the most appropriate media and methods. Moreover, learning environment has lo be able to give comfort, safety, fun and challenge.